Impact of the COVID-19 pandemic on tuberculosis services in a rural area of Senegal - Menotti, Giulia; Giglia, Maddalena; Riccardi, Niccolò; Diop, Yacine Mar; Ndiaye, Mamadou; Gning, Lamin; Diaw, Mama Moussa; Fumagalli, Giovanni; Saderi, Laura; Sotgiu, Giovanni; Besozzi, Giorgio; Tadolini, Marina (Le infezioni in medicina, 2025)
The Coronavirus (COVID-19) pandemic significantly impacted on tuberculosis (TB) services (TB) services in both high and low TB burden countries. Objectives: This study aimed to investigate the impact of COVID-19 on TB outpatient services in terms of new TB case notifications and treatment outcomes in a rural area of Senegal. A retrospective observational study was conducted at the Health Care Centre of Diofior (HCD) in the Fimela district, Fatick Region (Senegal), covering the period from January 1st, 2018, to December 31st, 2022. Data were divided into pre-COVID-19 (until March 31st, 2020) and during-COVID-19 (from April 1st, 2020) periods for analysis. Among the 246 TB cases included (63.4% male, median age 38.4 years), 94 (38.2%) had been diagnosed in the pre-COVID-19 period and 152 (61.8%) in the during-COVID-19 period. In 2020, TB case notifications dropped by 24.4% compared to 2019, followed by an increase of 70.6% in 2021 and 91.2% in 2022. The TB treatment success rate decreased from 85.1% before COVID-19 to 77.6% in during-COVID-19 period. Moreover, mortality increased from 2.1% to 5.3%, and the lost-to-follow-up rate rose from 8.5% to 14.5% between the pre- and during-COVID-19 periods. Although the number of COVID-19 cases reported in Senegal was relatively low in the study period compared to other settings, our study indicates that the pandemic had a significant impact on TB services in this rural area of Senegal.